Honokiol Induces Ferroptosis by Upregulating HMOX1 in Acute Myeloid Leukemia Cells - Lai, Xingrong; Sun, Yanhua; Zhang, Xuedi; Wang, Dan; Wang, Jialing; Wang, Haihua; Zhao, Yao; Liu, Xinling; Xu, Xin; Song, Haoran; Ping, Wenjia; Sun, Yanli; et al. (Frontiers in Pharmacology, 2022)
Acute myeloid leukemia (AML) is one of the malignant hematological cancers with high mortality. Finding a more effective and readily available treatment is of the utmost importance. Here, we aimed to identify the anti-leukemia effect of a natural small molecule compound honokiol on a panel of AML cell lines, including THP-1, U-937, and SKM-1, and explored honokiol's potential biological pathways and mechanisms. The results showed that honokiol decreased the viability of the targeted AML cells, induced their cell cycle arrest at G0/G1 phase, and inhibited their colony-formation capacity. Honokiol also triggers a noncanonical ferroptosis pathway in THP-1 and U-937 cells by upregulating the level of intracellular lipid peroxide and HMOX1 significantly. Subsequent studies verified that HMOX1 was a critical target in honokiol-induced ferroptosis. These results reveal that honokiol is an effective anti-leukemia agent in AML cell lines and may be a potential ferroptosis activator in AML.